1995
DOI: 10.1006/jmbi.1994.0128
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Crystallization and Preliminary X-ray Analysis of Penicillin Binding Protein 4 fromEschericha coli,a Protein Related to Class A β-Lactamases

Abstract: Crystals of the penicillin binding protein 4 (PBP4) fromto six weeks. They belong to space group C222 with cell dimensions a = 68.5 Å, b = 100.5 Å and c = 137.0 Å, and diffract to at least 2.8 Å resolution. There 9747 AG Groningen is one molecule with a molecule mass of 49,568 Da in the asymmetric unit. The Netherlands

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Substrate binding can be a key determinant in the localization of proteins [18,65,66]. To test whether PBP4 substrate binding is needed to localize at division sites we expressed the active site mutants PBP4(S62G) and (S62A) [61] that fails to bind b-lactams and therefore is not able to hydrolyze the PG stem peptide (Fig. S2 and S3).…”
Section: Pbp4 Localizes Between the Peptidoglycan Layer And The Outer Membranementioning
confidence: 99%
See 1 more Smart Citation
“…Substrate binding can be a key determinant in the localization of proteins [18,65,66]. To test whether PBP4 substrate binding is needed to localize at division sites we expressed the active site mutants PBP4(S62G) and (S62A) [61] that fails to bind b-lactams and therefore is not able to hydrolyze the PG stem peptide (Fig. S2 and S3).…”
Section: Pbp4 Localizes Between the Peptidoglycan Layer And The Outer Membranementioning
confidence: 99%
“…A non-catalytical domain of unknown function (domain 2) is inserted into the transpeptidase domain 1, and a third domain (domain 3) is inserted into domain 2. Domain 3 is positioned above the active side with its catalytic serine 62, which resides in domain 1, and might be involved in substrate binding or regulation (56,57) (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%
“…X-ray structures of membrane-bound penicillin-binding proteins may soon appear, because water-soluble forms are being crystallized (12,22,36,86). In the meantime, given the similarity of the ␤-lactamase structures with the X-ray structure of the penicillin-inhibited DD-peptidase (25,46), one might speculate on the structural basis of mutations discovered in the low-affinity penicillin-binding proteins (24,81,82).…”
Section: Altered Penicillin-binding Proteinsmentioning
confidence: 99%
“…A non-catalytical domain of unknown function (domain 2), which is inserted into the transpeptidase domain 1, and a third domain (domain 3), which is inserted into domain 2. Domain 3 is positioned above the active site (Serine 62, in domain 1), and might be involved in substrate binding or regulation [ 58 , 59 ] ( Fig 1A ). Site directed mutagenesis suggested that residues from domain 1 (R361) and 2 (D155) are important for the endopeptidase activity [ 60 ].…”
Section: Introductionmentioning
confidence: 99%